Two new species of Acanthocreagris from Corsica and mainland France, and notes on some congeneric species (Pseudoscorpiones: Neobisiidae) - Gardini, Giulio (Fragmenta entomologica, 2022)
Two new species of the genus Acanthocreagris Mahnert, 1974 are described from Corsica (Acanthocreagris cyrnea sp. n.) and from the French department of Var (Acanthocreagris heurtaultae sp. n.). Specimens of Acanthocreagris cf. foghesa Gardini, 2018 and Acanthocreagris ruffoi (Lazzeroni, 1969) from Sardinia and Sicily, respectively, are described and depicted. Acanthocreagris lanzai (Beier, 1961) is newly recorded from Piedmont, Acanthocreagris microphthalma Callaini, 1986 from Marche and Umbria, Acanthocreagris ruffoi from Marche and Campania.